The Interpretation of Children’s Utterance by Watching Religious Film - DEASY YUNITA SIREGAR (VISION, 2016)
The children are able to interpret the message from the religious film that they watched depends on what interpretation is intended to achieve, provocation to thought, an enjoyable experience. And their utterances are affected by some factors (functional, structural, situational, and personal) that lead the different interpretation they have produced